PENGARUH CORPORATE SOCIAL RESPONSIBILITY TERHADAP PENGHINDARAN PAJAK PERUSAHAAN DENGAN DIREKTUR WANITA SEBAGAI VARIABEL MODERASI (Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Tahun 2022-2024) - Triyanti Maria Natalia Siregar; Wahyu Meiranto (Diponegoro Journal of Accounting, 2026)
Taxes are the primary source of state revenue and play a crucial role in supporting development and public welfare. However, tax revenue in Indonesia has not yet been optimal due to the presence of corporate tax avoidance practices, where taxes are perceived as a burden that reduces profits. This study examines the factors influencing tax avoidance through corporate social responsibility and the role of women directors in moderating this relationship. This research employs a quantitative approach using panel data regression, analyzed with EViews 13 software. The sampling technique used is purposive sampling, resulting in a total sample of 51 manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the 2022–2024 period. The findings indicate that corporate social responsibility has a negative effect on corporate tax avoidance. This suggests that companies with higher levels of social responsibility tend to be more compliant with tax obligations. However, the role of women directors does not show a significant effect in moderating the negative relationship between corporate social responsibility and corporate tax avoidance.